Endoscopic extraction of adjustable gastric bands after intragastric migration as a complication of bariatric surgery: technique and advice - Collado-Pacheco, David; Rábago-Torre, Luis Ramon; Arias-Rivera, Maria; Ortega-Carbonel, Alejandro; Olivares-Valles, Ana; Alonso-Prada, Alicia; Vázquez-Echarri, Jaime; Herrera-Merino, Norberto (Endoscopy International Open, 2016)
Background: Surgery has been the method most widely used to manage the extraction of gastric bands with inclusion as a late complication of bariatric surgery; however, surgical extraction entails morbidity and limits future surgical procedures. The development of endoscopic techniques has provided an important means of improving the treatment of this complication, enabling minimally invasive and safe procedures that have a high success rate.Methods: A retrospective analysis was conducted of patients who had laparoscopic gastric banding complicated by intragastric migration and were treated endoscopically. A technique already described for managing this complication was employed. An MTW Endoskopie Dormia basket for mechanical lithotripsy or a standard 0.0035-in guidewire was placed around the band, and an MTW Endoskopie emergency lithotripter was used to section it, after which the band was extracted with a standard polypectomy snare. Also analyzed were the initial symptoms of patients with this complication, the mean time from surgery to development of the event, the success rate of endoscopic treatment, and complications,Results: A total of 127 patients had undergone gastric banding surgery in our Bariatric Surgery Center; of these, 12 patients (9.4 %) developed a complication such as intragastric migration of the band. Weight gain and pain were the main symptoms in 11 patients (92 %), and the mean time to the development of symptoms was 51.3 months. A single endoscopic treatment was successful in 7 of 9 patients (78 %). Only 1 complication, involving ventilation during anesthesia, occurred; no other adverse events were recorded.Conclusions: The endoscopic extraction of bands with inclusion is feasible and can be performed easily and successfully. The procedure is available in all hospitals and has a low incidence of related complications, so that unnecessary surgical procedures can be avoided.